2016
DOI: 10.1007/s00198-016-3669-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a standardized order set for the management of non-hip fragility fractures in a Fracture Liaison Service

Abstract: SummaryWe analysed the impact of a standardized order set empowering staff nurses to independently manage a Fracture Liaison Service over a 9-month period. Nurses identified between 30 and 70 % of non-hip fragility fractures to the unit in charge of management over time. The latter managed 58 % of referred patients.IntroductionThe main goal of this study was to evaluate the impact of a standardized order set empowering nurses to independently manage a fracture liaison service (FLS).MethodsSince November 2014, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Participants sustaining multiple FFs during a single event were counted only once; major FFs took precedence over fractures at other sites [ 31 ]. Data related to the FLS coordinators’ professional background were obtained, i.e., nurses with a standardized order set for the initiation of osteoporosis treatment [ 32 ] or other disciplines without a similar prescription tool (biomedical specialist or physiotherapist). Data related to adherence to FLS recommendations were also extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Participants sustaining multiple FFs during a single event were counted only once; major FFs took precedence over fractures at other sites [ 31 ]. Data related to the FLS coordinators’ professional background were obtained, i.e., nurses with a standardized order set for the initiation of osteoporosis treatment [ 32 ] or other disciplines without a similar prescription tool (biomedical specialist or physiotherapist). Data related to adherence to FLS recommendations were also extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Results from the 2017 UK national audit of FLSs demonstrated that only 6% of submitted patients had a sentinel vertebral fracture, 41% of patients were monitored within 16 weeks of index fracture, and 31% had initiated therapy [5]. Improving detection of vertebral fractures is likely to require integration with radiology systems [43]; reducing the time to treatment is likely to need integration of FLS directly into existing orthopaedic pathways, minimising additional clinical workup [44]. While the benefits of potent AOMs in the setting of a recent fracture have not been formally tested, subgroup analyses from studies stratified by recency of fracture have been encouraging [34,45].…”
Section: Dear Editormentioning
confidence: 99%
“…Despite varying models, a common theme within these programs is that they are usually coordinated by a specified individual, usually a clinical nurse specialist, who will be case-finding, working to prescribed protocols, with assistance and referral access to specialist physicians 11. The “4i” Lucky Bone FLS in Montreal, Canada, demonstrated that there was overwhelming consensus between their physicians and the decisions made by their specialist nurses when they were empowered within a system involving an order set to allow them to investigate and manage patients,24 suggesting that such a service can be safely and efficiently run with minimal supervision from physicians 35. In terms of identifying patients at risk of osteoporosis, most services would initiate an assessment in patients over the age of 50 years presenting with a fragility fracture,21,25,26,28 although some centers also included women as young as 40 22.…”
Section: Models Of Flsmentioning
confidence: 99%